Lipid A decreases human erythrocytes deformability by increasing intracellular Ca2+: Effects of verapamil, staurosporine and the rho-kinase inhibitor Y-27632 - Ruef, Peter; Ehrhard, M.; Frommhold, David; Koch, L.; Fritzsching, Benedikt; Pöschl, Johannes (Clinical hemorheology and microcirculation, 2011)
There are several reports demonstrating an involvement of bacterial toxins in the rigidity of red blood cells (RBC). The present study investigates the influence of E. coli F-583-Rd lipid A on RBC deformability under mechanical shear stress. Verapamil (Ca2+ channel inhibitor), staurosporine (protein kinase inhibitor) and Y-27632 (rho-kinase inhibitor) were used to modify the effect of lipid A on RBC deformability. We also determined if E. coli F-583-Rd Lipid A could induce an increase of intracellular Ca2+ concentration. For the deformation measurements RBC (10 adult donors) were incubated with E. coli F-583-Rd lipid A (100μg/ml) and also co-incubated with either verapamil (10-7 mol/l), staurosporine (10-7 mol/l) or Y-27632 (10-7 mol/l). The deformation of the RBC under different shear stresses (0.6-60 Pa) was measured by a shear stress diffractometer (Rheodyne SSD). Intracellular Ca2+ was determinded by flow cytometry in RBC incubated with Lipid A and labeled with fluorescent Fluo-4/AM which binds intracellular Ca2+ with high affinity resulting in enhanced green fluorescence intensity. At increasing shear stresses Lipid A induced a significantly lower elongation. Co-incubation of the erythrocytes with verapamil or staurosporine inhibited lipid A induced decrease in elongation while Y-27632 had no effect. Verapamil, Staurosporine and Y-27632 did not influence the elongation response of the cells under control conditions. Lipid A induced a marked increase in fluorescence Fluo-4/AM indicating increased intracellular Ca2+. These results suggest that E. coli F-583-Rd lipid A is able to influence red blood cell rigidity by a rapid and significant increase of intracellular Ca2+ concentration. Verapamil and staurosporine abolished the decrease in deformability of Lipid A incubated RBC.
Gesehen am 21.09.2022
Im Titel ist der Ausdruck "2+" hochgestellt